1999
DOI: 10.1093/jnci/91.14.1194
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Smoke Carcinogens and Lung Cancer

Abstract: The complexity of tobacco smoke leads to some confusion about the mechanisms by which it causes lung cancer. Among the multiple components of tobacco smoke, 20 carcinogens convincingly cause lung tumors in laboratory animals or humans and are, therefore, likely to be involved in lung cancer induction. Of these, polycyclic aromatic hydrocarbons and the tobacco-specific nitrosamine 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone are likely to play major roles. This review focuses on carcinogens in tobacco smoke a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
925
2
23

Year Published

2000
2000
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,700 publications
(1,007 citation statements)
references
References 139 publications
27
925
2
23
Order By: Relevance
“…[22][23][24] The presence of CYP1A2 and CYP3A4 in intestinal metaplasia suggests that CYP1A2 and CYP3A4 may play a role in the early stages of gastric carcinogenesis by activating nitrosamines to mutagenic products. 25 It has been postulated that gastric cancer is the end result of a pre-cancerous sequence of events: superficial gastritis, chronic atrophic gastritis, intestinal metaplasia and dysplasia. 26 These lesions are prevalent in populations at a high risk for gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] The presence of CYP1A2 and CYP3A4 in intestinal metaplasia suggests that CYP1A2 and CYP3A4 may play a role in the early stages of gastric carcinogenesis by activating nitrosamines to mutagenic products. 25 It has been postulated that gastric cancer is the end result of a pre-cancerous sequence of events: superficial gastritis, chronic atrophic gastritis, intestinal metaplasia and dysplasia. 26 These lesions are prevalent in populations at a high risk for gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco, a rich resource of pulmonary carcinogens, is known to cause many genetic changes through DNA mutations (Hecht, 1999). It has been also demonstrated that tobacco exposure induces epigenetic changes through promoter methylation of tumor suppressor genes (TSGs) Belinsky et al, 2003;Fujiwara et al, 2005) and proapoptotic genes (Pulling et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 presents a schematic that links nicotine addiction with lung cancer by way of cigarette smoke carcinogens [Hecht, 1999]. Nicotine addiction is the reason that people continue to smoke, in spite of the well-documented health risks.…”
Section: Introductionmentioning
confidence: 99%